أثر الحجامة الجافة في علاج تشنج عضلات الظهر العلوية للرياضيين - حمزة، حيدر عبد علي; صالح، قاسم محمد; عباس، عصام طالب (الأكاديمية الدولية لتكنولوجيا الرياضة, 2019)
The aim of the study was the use of dry cupping in the treatment of muscle spasms in the upper back area near the shoulder pad and its impact on the athletes suffering from these pains. Researchers have hypothesized that dry cupping has a positive effect in reducing the spasticity of the upper back muscles of athletes. The researchers used the one-group experimental method and identified the research community in athletes with muscular spasm in Babil Governorate. The sample of the study included (15) injured patients who were selected by deliberate method. The researchers used the form of pain measurement according to the Shopper test and physical tests. The researchers used the statistical program spss and used the following statistical methods (arithmetic mean, standard deviation, T test for interrelated samples) . The researcher concuded that Cupping has a great role in muscle relaxation, reducing the level of cramping and pain of upper back muscles and improving the motor flexibility of athletes.The researcher recommended the need to use dry cupping or wet types in the treatment of muscle spasms, and get benefit from cupping in the activation of blood circulation in the main working muscles of performance.
هدف دراسة البحث الى استخدام الحجامة الجافة في علاج التشنجات العضلية في منطقة الظهر العلوية القريبة من لوح الكتف ومعرفة تأثيرها على الرياضيين المصابين بتلك الالام وقد افترض الباحثون للحجامة الجافة تأثيرا ايجابيا في خفض الام التشنج لعضلات الظهر العلوية للرياضيين اما منهجية البحث فقد استخدم الباحثون المنهج التجريبي ذو المجموعة الواحدة وحدد مجتمع البحث بالرياضيين المصابين بالتشنج العضلي في محافظة بابل ولغت عينة البحث(15) لاعب مصابا تم اختيارهم بالطريقة العمدية واستخدم الباحثون استمارة قياس درجة الألم وفق اختبار شوبر والاختبارات البدنية وتضمن المنهج استخدام الحجامة الجافة لمرة واحدة على العضلة المصابة بالتشنج العضلي واستخدم الباحثون البرنامج الاحصائي ال SPSS ومنه استخدم الوسائل الاحصائية التالية (الوسط الحسابي، الانحراف المعياري واختبار T للعينات المترابطة) اما اهم الاستنتاجات التي توصل اليها الباحثون هي: 1-للحجامة دور كبير في بالاسترخاء العضلي وخفض مستوى التشنج والالم لعضلات الظهر العلوية وتحسين المرونة الحركية للرياضيين أما اهم التوصيات الي اوصى مها الباحثون أن هي: 1-ضرورة استخدام الحجامة بنوعيها الجافة او الرطبة في علاج التشنجات العضلية 2-الاستفادة من الحجامة في تنشيط الدورة الدموية في العضلات الرئيسية العاملة في الاداء.
Keywords: الحجامة الجافة -- الاسترخاء العضلى -- آلام الظهر التشنجات العضلية